One Hundred Years of Social Protection The Changing Social Question in Brazil, India, China, and South Africa - Leisering, Lutz (Global Dynamics of Social Policy, 2021)
While the rise of social protection in the global North has been widely researched, we know little about the history of social protection in the global South. This volume investigates the experiences of four middle-income countries - Brazil, India, China and South Africa - from 1920 to 2020, analysing if, when, and how these countries articulated a concern about social issues and social cohesion. As the first in-depth study of the ideational foundations of social protection policies and programmes in these four countries, the contributions demonstrate that the social question was articulated in an increasingly inclusive way. The contributions identify the ideas, beliefs, and visions that underpinned the movement towards inclusion and social peace as well as counteracting doctrines. Drawing on perspectives from the sociology of knowledge, grounded theory, historiography, discourse analysis, and process tracing, the volume will be of interest to scholars across political science, sociology, political economy, history, area studies, and global studies, as well as development experts and policymakers.